First report of Phytopythium helicoides causing root and crown rot on Rhododendron in Ohio and the United States - Capouya, Rachel (Plant disease, 2024)
Rhododendron is a diverse genus of evergreen and deciduous species grown in gardens worldwide for their attractive flowers and foliage. In summer 2023, nine of 12 potted Rhododendron 'Nova Zembla' plants purchased from a wholesale nursery in Ohio exhibited wilting, leaf and stem discoloration, and severely darkened and softened roots, which eventually progressed into dieback and plant death. Roots tested positive with a Phytophthora Immunostrip® (Agdia, Inc.), a common serological test for oomycete root rots. Roots were surface disinfested by soaking in 10% bleach for 30 s, rinsed three rinses in sterile water, then sectioned into small pieces and plated on oomycete-selective PARP-CMA medium (Ivors, 2015). Pure cultures were obtained by transferring hyphal tips onto potato dextrose agar (PDA) and incubating at 23 ± 2 °C under fluorescent light (12 h) for one week. Colonies on PDA displayed radiate to petaloid radial growth with minimal aerial aseptate mycelia. Sporangia production was induced by flooding mycelial plugs with sterile 10% V8 broth and incubating in the dark for 48 h at 23 ± 2 °C. The resulting mycelial mat was rinsed three times with sterile water then mounted on glass slides. Sporangia were terminal, globose and rarely obovoid, papillate or non-papillate, and measured 22.24-46.38 µm in length and 19.80-33.70 µm in width (n=35). Oospores were not observed in culture after 1 week of incubation at room temperature. DNA was extracted using the QIAGEN DNEasy Plant Mini Kit from mycelial mats grown in potato dextrose broth for 7 days at 26°C with 70 rpm shaking followed by straining. PCR and bidirectional sequencing were conducted with primers OomCOILevup/FM85mod (mtDNA COX1 region; Robideau 2011), and NL1/NL4 (rDNA D1-D2 large subunit; O'Donnell 1993). NCBI BLAST searches of the LSU and COX1 consensus sequences had 100% (637/637 bp; PQ381277) and 98.33% (708/720 bp; PQ383368) match, respectively, to the type strain of Phytopythium helicoides PF-he2 (OM337587.1, GCA_024867545.1). Five of the nine plants yielded isolates identified as P. helicoides by sequencing. Isolate FPH2023-33 was selected for in-depth characterization. Pathogenicity tests were conducted once using young (<6" height and diameter) Rhododendron 'PJM Elite Star' (n=6), and once using 'Cherries and Merlot' (n=6) plants. Plants were inoculated by placing five, 5-mm agar plugs taken from 3-day old V8 agar cultures or sterile V8 agar plates (control) into the root area of each plant. Plants were maintained in flood trays under saturated soil conditions for 30 days in the greenhouse at an average of 24°C and 70% RH. Uninoculated plants were kept in separate trays to prevent cross-contamination. At 30 DPI, 75% of inoculated 'PJM Elite Star' plants showed severe leaf curl and wilting, and 100% had darkened and weakened root systems, while 50% of inoculated 'Cherries & Merlot' plants showed stunting, and 75% showed mild discoloration of the roots and crown. Control plants of both cultivars remained asymptomatic. Phytopythium helicoides was re-isolated from all inoculated plants and confirmed to be identical to the original isolate using the same methods described above. No Phytopythium was recovered from the control plants. This is the first report of this pathogen causing root rot on Rhododendron in the United States. As chemical and cultural control practices for this recently described pathogen are not yet well-studied, its presence may have a significant impact in both nursery production and landscape settings